Pharmacological Potential of Inonotus Obliquus: An Integrative Review of Antitumour, Immunomodulatory and Anti-Inflammatory Effects - Osipova, Daniella; Shakhbanova, Asiyat; Yunusova, Alina; Shakhbanov, Shakhban; Alieva, Leyla; Skovorodko , Polina; Parshenkov, Mike (Scripta Medica, 2026)
Inonotus obliquus (Chaga mushroom), long used in traditional medicine, has recently gained substantial scientific attention due to its diverse pharmacological activities. While numerous preclinical studies exist, the lack of a comprehensive understanding of its molecular mechanisms continues to hinder clinical translation. This review summarises current evidence on the antitumour, immunomodulatory, anti-inflammatory and antioxidant effects of I obliquus, with emphasis on the underlying cellular pathways. The pharmacological activity of Chaga is mediated by a complex array of bioactive compounds that collectively induce apoptosis and cell-cycle arrest in cancer cells, modulate the complement system, suppress pro-inflammatory mediators in macrophages and enhance antioxidant defence mechanisms. These effects result from multifactorial and often synergistic interactions with key signalling cascades, including nuclear factor-kappa B (NF-kB), mitogen-activated protein kinase (MAPK) and PI3K/Akt pathways. Although experimental data are promising, the translation of I obliquus from a traditional remedy into standardised therapeutic formulations is constrained by chemical variability and a lack of robust clinical validation. Continued multidisciplinary research is essential to elucidate its pharmacological potential and to position Chaga as a valuable source of novel therapeutic agents in modern medicine.